Nursing diagnoses in primary health care consultations to newborns - Priscila Costa; Amanda Pereira Duarte; Aline Santa Cruz Belela-Anacleto; Paula Rosenberg de Andrade; Maria Magda Ferreira Gomes Balieiro; Maria De La Ó Ramallo Veríssimo
ABSTRACT Objective: To describe and analyze nursing diagnoses established on newborns' medical consultations in a primary health care service. Method: Descriptive, analytical and quantitative study performed in a primary health care clinic in São Paulo. Data were collected from the medical records of 37 children treated in 39 nursing consultations during their neonatal period. The identified nursing diagnoses were analyzed regarding: frequency, classification in strengthening or exhaustion in light of the health-disease process, and the correspondence with the essential needs of infants. Results: 372 diagnoses were identified, most of them of strengthening (71%), such as efficient development (n = 37) and effective growth (n = 36). Among the exhaustion diagnoses (29%), there was a predominance of risk for suffocation (n = 15) and impaired tissue integrity (n = 14). Most diagnoses corresponded to the need of physical protection and security. Conclusion: Families are strengthened in the care of the essential needs of newborns, however, preventing diseases is necessary.